Assessing the Influence of Selected Human Capital Management Factors on the Organizational Performance of Higher Education Sector in Afghanistan - MOHAMMAD QASIM AYAZ; ABDUL QAHAR; DR. RAZA ULLAH; DR. MUSTAFA AFEEF (Journal of Business & Tourism, 2021)
Human resources are found to be one of the most fundamental contributors in the success of any organization. In the context of the education sector, the importance to be attributed to the potential human capital and its management is ever-increasing. The main purpose of the study is to establish the influence of human capital management on performance of an organization, particularly within the education sector of Afghanistan. For this purpose, 20 universities were selected, amongst which 10 universities were private and the rest 10 were government institutions. The study used questionnaire method to collect the required data from selected public and private universities in Afghanistan. Three hundred employees were sampled from various higher education institutions of the country, both public and private and the data were analyzed through SPSS 16 version. The findings of the study depict a strong positive relationship between human capital management and organizational performance.